1977
DOI: 10.1111/j.1346-8138.1977.tb01037.x
|View full text |Cite
|
Sign up to set email alerts
|

A STUDY ON THE CHARACTERIZATION OF CORYNEBACTERIUM ACNES

Abstract: Forty-nine strains of anaerobic gram-positive rods were used in a systematic study of their biochemical and physiological reactions and morphological characteristics and were also subjected to gas chromatographic analyses in an effort to classify them as strains of Corynebacterium acnes (C. acnes). The strains were isolated both from lesions in acne vulgaris and from normal skin. According to their biochemical and physiological characters, these 49 strains were divided into six subgroups (Subgroup A-F). They w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

1979
1979
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
(10 reference statements)
1
5
1
Order By: Relevance
“…Cummins and Johnson found that sorbitol fermentation was useful for the assay of serotypes of P. acnes (2). However, the substantial proportion of strains of serotype I were usually sorbitol fermentation negative (2,8,14). In our study also, only 54% of the strains of serotype I were sorbitol fermentation positive.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Cummins and Johnson found that sorbitol fermentation was useful for the assay of serotypes of P. acnes (2). However, the substantial proportion of strains of serotype I were usually sorbitol fermentation negative (2,8,14). In our study also, only 54% of the strains of serotype I were sorbitol fermentation positive.…”
Section: Discussioncontrasting
confidence: 58%
“…Three reports on biotyping of P. acnes have appeared in the literature (10,13,14). However, strains of P. granulosum were confused with P. acnes, as in the case of serotyping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indole, nitrate, milk, and gelatin hydrolysisnegative P. acnes isolates have been reported by other investigators (7,10,12,21), but in our present work, these reactions were positive on all isolates of P. acnes. On the other hand, these reactions were negative on all isolates of P. granulosum.…”
Section: Ampicillinsupporting
confidence: 65%
“…For example, the diluent for aerobes first described by Williamson and Kligman (26) has been used for isolation of propionibacteria without further examination of the suitability of the composition and of the conditions used. Although the problems pertaining to the taxonomy of Propionibacterium acnes were largely dealt with by Johnson and Cummins in 1972 (2, 8, 13-15, 18, 20), it is apparent in the literature that there are circumstances in which Propionibacterium granulosum are often confused with P. acnes (1,21,24,25).…”
mentioning
confidence: 99%